Pengaruh Kualitas Pelayanan dan Kepercayaan Konsumen terhadap Loyalitas Pelanggan pada SRC Bahtera di Kecamatan Bantarkalong Tasikmalaya - Rika Fitriani; Raskadi R (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The increasingly intense competition in the retail business requires business players to improve service quality and build consumer trust in order to create customer loyalty. This study aims to find out the effect of service quality and consumer trust on customer loyalty at SRC Bahtera in Bantarkalong District, Tasikmalaya. The research method used is a descriptive verificative method with a quantitative approach. Data was collected through distributing questionnaires to 98 respondents selected using purposive sampling. Data analysis was carried out using IBM SPSS Statistics version 25 through validity tests, reliability tests, normality tests, correlation analysis, multiple linear regression analysis, determination coefficients, partial tests (t-tests), and simultaneous tests (F-tests). The research results show that service quality and consumer trust, both partially and simultaneously, have a positive and significant effect on customer loyalty. The relationship between service quality and consumer trust falls into the strong category, while the determination coefficient results indicate that these two variables contribute 53.6% to customer loyalty, with the remaining 46.4% influenced by factors outside the study.